Water Coordination for a Changing Hydrology. (2nd April 2013) - Napolitano, Grace F.
Abstract : With increasing frequency, we are hearing reports and declarations about the real and impending impacts associated with changing hydrologic and physical systems. Droughts are forecasted to expand and persist, storms are increasing in frequency and intensity, and reservoirs are draining, filling up with sediment, or overflowing. The obvious conclusion is that we are in a changing, dynamic time regarding water, weather, and climate.